Communication Patterns of Lecturers in German Competence Teaching at the University - Saleh, Nurming; Usman, Misnawati; Achmad, Abd. Kasim (Indonesian Journal of Educational Studies, 2023)
Abstract. This study aims to obtain data and information related to lecturer communication patterns in German competence teaching. The course is focused on German language competence, consisting of four competencies: reading (Lesen), listening (Hören), writing (Schreiben), and speaking (Sprechen). The research was conducted in the German Language Education Study Program at the Faculty of Language and Literature. The results showed that the communication patterns used by lecturers in German competence teaching included as many as 291 communication patterns with details: primary communication patterns as many as 91 (verbal as many as 69 and nonverbal as many as 22), secondary communication patterns as many as 69, interpersonal communication patterns as many as 20, linear communication patterns as many as 49, and circular communication patterns as many as 61. The use of communication patterns by lecturers in German competence teaching from the highest to the lowest levels is primary communication patterns (31%), secondary communication patterns (24%), circular communication patterns (21%), linear communication patterns (17%), and interpersonal communication patterns (7%).